Household transmission of SARS-CoV-2 in the third wave of the pandemic with special reference to clinico-epidemiological characteristics - Suvarna A Joshi; Pooja G Shah; Mayuri R Gajbhiye; Praveena Pillai; Sonali N Dudhate; Rajesh P Karyakarte (Wolters Kluwer Medknow Publications, 2024)
Background: Coronavirus disease 2019 (COVID-19) pandemic began in India in 2020. Despite successful vaccination, cases again started increasing from mid-December 2021. Therefore, this study was undertaken to find out the clinico-epidemiological characteristics and effectiveness of vaccination in the household transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in and around Pune. Material and Methods: All samples received from December 15, 2021, till February 15, 2022, were included in the study. Samples received in viral transport medium (VTM) were extracted by the MagMAX RNA Extraction Kit, and reverse transcriptase-polymerase chain reaction (RT-PCR) was performed by the CoviPath Kit as per kit guidelines. Values of nucleocapsid (N) gene and open reading frame (ORF) less than 37 were considered positive. Clinico-epidemiological data were analyzed from the sample referral form (SRF). Results: A total of 712 of 1032 household contacts of 271 families were positive. When geographical areas were compared, it was found that rural areas were affected more (63.76%) as compared to urban areas (36.24%). Males were more affected than females. The most commonly affected age group was 41-50 years (26.54%). Small families were found to have more household transmission. Mild symptoms were present in 97.89%. Among 271 infected individuals, seven were admitted to hospital, of which one patient died due to pneumonia. Two doses of vaccination were completed in 93.95%, and 3.79% had taken booster dose. Conclusions: Data from this study showed that a high rate of transmission was observed in household contact despite two doses of vaccination. However, these vaccinated individuals had mild symptoms, maybe due to the effect of vaccination and infecting variant omicron.